Excel Solver Wizard Model Development for Abeokuta's Rainfall Intensity, Duration and Frequency - David, A. O.; Opafola, O. T.; Odugbose, B. D.; Akisanya, O. O.; Kadir, D. A. (NIU Journal of Social Sciences; Vol 10 No 2 (2024): NIU Journal of Social Sciences, Vol. 10 No. 2, June 2024DO - 10.58709/niujss.v10i2.1867, 2024)
In hydraulic engineering systems, the kind and speed of water flow that results from rainfall activity in a particular catchment are constant variables. Twenty-five (25) years' worth of Abeokuta daily rainfall data (amount and duration) were provided by the Nigerian Meteorological Agency (NIMET), Abuja. After that, frequency analysis was performed on this data to produce intensity-duration-frequency models. The Excel Optimization Solver wizard was used to get the mean rainfall levels for the following time intervals: 5, 10, 15, 20, 30, 45, 60, 90, 120, 180, 240, 300, and 420 minutes. The data was then subjected to frequency analysis. For return periods of 2, 5, 10, 25, 50, and 100 years, defined and non-specified IDF models were created using the Normal distribution and Pearson type 3 distributions. Abeokuta has not witnessed these models' development. Values of the mean squared error (MSE) and coefficient of determination (R 2 ) were used to assess the probability distribution functions' fitness. The normal distribution has R 2 and MSE values between 0.977 and 0.991 and 85.73 and 118. 14, but the Pearson type 3 distribution has values between 0.964 and 0.997 and   42.88 and 118.68. It is recommended that the Ministry of Works utilize probability distribution models to anticipate rainfall intensities in the city of Abeokuta, in order to set acceptable design objectives. Keywords: Excel Optimization Solver, Normal distribution, Pearson Type 3 distributions, Goodness of fit test, IDF models, Abeokuta.